Manajemen dan Rencana Pengembangan Taman Publik untuk Meningkatkan Imunitas Masyarakat Pasca-Pandemi Covid-19 di Kota Bogor - Aghnina Rahmatika; Hadi Susilo Arifin; Nurhayati (http://arl-faperta.ipb.ac.id/, 2025)
The purpose of this research is to inventory three macro-scale public parks in order to improve them as productive landscape, a kind of landscape services; and to propose park management strategy in the post pandemic Covid-19. This research was conducted from January to June 2023, and extended to December 2023. The study sites are Alun-Alun Kota Bogor, Lapangan Sempur and Taman Kencana; and developed to all public parks in Bogor City. Field survey results of bio-physical and social-cultural aspect had be analyzed descriptively and statistically. The final result of this research is a macro scale public parks management strategy to increase post pandemic community immunity. The management strategies for the three public green spaces can be enhanced by understanding visitor characteristics. Alun-Alun Bogor is generally visited by families with young children, therefore the additional of active facilities is necessary. Furthermore, this spacious green open area lacks shade, so the inclusion of shading vegetation is needed to enhance visitor comfort. Lapangan Sempur is primarily frequented by students who seek exercise or gathering spaces, hence the addition of seating facilities should be considered to accommodate visitors. Taman Kencana is preferred by working individuals and retirees who enjoy sitting and relaxing with their children and grandchildren. To maximize the potential of the park, it is advisable to provide more toilet facilities and prayer rooms. In addition, visitors of all three parks desire providing instagrammable spots, it considere as a recommendation.